The association of socioeconomic deprivation with access and survival after hematopoietic stem cell transplantation in New Zealand. Issue 2 (12th June 2022) - Belyaev, Andrei M.; Lewis, Clinton; Doocey, Richard; Bergin, Colleen J.
Abstract: Background: Socioeconomic deprivation (SED) is a risk factor for reduced survival of hematopoietic stem cell transplant (HSCT) recipients. This study aimed to evaluate access and long‐term survival of HSCT recipients. Methods: This was a hospital HSCT Registry‐based retrospective cohort study. Patients who underwent HSCT from January 2010 to June 2020 were identified. HSCT recipients younger than 16 years of age, patients who reported their residential address as a post office box or the Department of Corrections, and those who left the country after HSCT were excluded from the study. HSCT recipients with the 2018 New Zealand deprivation index (NZDep2018) deciles 8, 9, and 10 were assigned to the higher SED group and those with NZDep2018 deciles from 1 to 7 were allocated to the lower SED group. The total number of New Zealanders in the higher and lower SED strata was obtained from the 2018 Census. Results: Eight hundred fifty‐one HSCT recipients met the eligibility criteria. HSCT recipients from the higher and lower SED strata of the New Zealand population had similar access to HSCT (odds ratio = .9; 95% confidence interval (CI): .77–1.04; p = .155). Mortality in the higher and lower SED groups of HSCT recipients was 9.6/100 person‐years (95% CI: 7.7–12/100 person‐years) and 8.1/100 person‐years (95% CI: 6.9–9.4/100 person‐years), respectively. The mortality ratio was 1.2 (95% CI: .9–1.6), p = .098. Both groups had similar survival. Conclusion: New Zealand residents from the higher and lower SED strata have similar access to HSCT. SED is not associated with reduced survival in adult HSCT recipients. Abstract : We have shown that New Zealanders from higher and lower socioeconomic deprivation (SED) strata had similar access to haemotopoietic stem cell transplantation (HSCT). HSCT recipients from the higher and lower SED groups had similar mortalities and overall survival.